The relationship between emotion regulation and relational aggression: a systematic literature review - Ahmad Zaki, Azimah; Ismail, Nellie; Arshat, Zarinah (Human Resources Management Academic Research Society (HRMARS), 2024)
Relational aggression poses significant risks to mental health and social peace. The ability to regulate emotion effectively has an effect on reducing adolescents’ engagement in relational aggression. Yet, no systematic reviews were found on the link between emotion regulation and relational aggression in adolescents. Thus, this study aims to analyse the existing body of work on the association between emotion regulation and relational aggression in adolescents. Following the ROSES (Reporting Standards for Systematic Evidence Syntheses) reporting standards protocol and several systematic literature review guidance papers, 14 databases and search engines identified 8 relevant articles. Though the analysis revealed some mixed results, the majority of the studies reported that emotion regulation and its different strategies determine whether adolescents engage in relational aggression or not. This review presents a systematic synthesis of the literature and provides insight into designing targeted interventions to enhance emotion regulation techniques, therefore reducing relational aggression engagement in adolescents.